Smooth turning path generation for agricultural vehicles in headlands. (November 2015) - Backman, Juha; Piirainen, Pyry; Oksanen, Timo
Abstract : Headland manoeuvring of agricultural vehicles is crucial when it comes to operational efficiency. Automatic guidance systems are usually able to parallel track but headland manoeuvring is not commonly included. Path tracking systems assume a feasible reference path can be followed but in some cases it is not trivial to generate such a path automatically. The Dubins Curves method is the traditional approach to generate the path, but this does not take into account parameters such as maximum steering rate. An algorithm is presented to generate a smooth path for headland manoeuvring where curvature and speed are continuous. Both the maximum steering rate and the maximum acceleration of the vehicle are taken into account. It is possible to define a target speed profile, either to increase or decrease the speed during the turn. The results present the functionality of the algorithm: two of the tests varied the ending pose and two others varied the parameters. The algorithm utilises numerical integration methods in one phase of the calculation, but it still generated paths in short computational time. The algorithm was found to be suitable both for use in real-time and in simulations since an average computational time of 0.36 s was achieved. Highlights: Automatic generation of swath-to-swath turning in agricultural field. Variable speed profile can be used to meet the requirements of real applications. Dynamic constraints of the actuators is taken into account. Proposed algorithm is fast enough for online or iterative applications.